Penolakan Notaris Muslim Terhadap Pembuatan Akta Ribawi (Perspektif UUJN Dan Hukum Islam) - Nelli Ayunda Putri (Universitas Islam Sumatera Utara, 2021)
The dualism of usury deed arrangement causes Muslim notaries to experience a dilemma about their obligations in making authentic deeds. The regulation regarding usury is only regulated in Islamic law, while positive law does not clearly regulate it. The problem in this thesis is the consideration of refusing to make a usury deed; conditions are allowed to make usury deed; and the legal consequences of refusing to make a deed of usury. This research is descriptive, namely normative juridical. Sources of secondary data and supplemented by primary data through interviews. The data collection technique used literature study and qualitative data analysis which was described descriptively. The consideration of refusing to make a deed of usury is contrary to Article 29 of the 1945 Constitution and the first precepts of Pancasila and the Qur'an and Hadith. The conditions that allow the making of a usury deed are to complete a cooperation agreement with the bank, emergencies and needs, a Muslim notary is responsible for the deed made. The legal consequence of refusing to make a deed of usury is that Notary Supervisory Board can be prosecuted and followed up and will avoid the sin of usury.Keywords: Rejection; Muslim Notary; Acts of Ribawi